Community Building Through Social Annotation: Building Academic Literacies at a Distance - Walsh Marr, Jennifer; Tan, Shihua (Canadian Journal of Learning and Technology / Revue canadienne de l’apprentissage et de la technologie, 2025)
Student readiness for university study cannot be assumed; the progression to become a successful student requires support. Highlighting the implementation of purposeful, accessible, and inclusive pedagogical design, this case study explores emergent academic literacies and community building using social annotation in the context of remote teaching and learning. This study analyses first year international students’ annotations in academic texts for indicators of learning and community in their asynchronous interactions with one another. Findings indicate that students were able to discern relevant aspects of meaning-making within their texts, pointing to developing academic literacies. Student threaded annotations, group work, and peer review demonstrated individual and shared learning developed over sustained engagement with one another. The study provides support for a curriculum that facilitates and supports novice scholar participation in university communities and discourses.